Pengembangan Program Monitoring Perkuliahan Berbasis Web di Jurusan Matematika FMIPA UNM Makassar - Asdar Asdar; Rosidah Rosidah; Fajar Arwadi (Seminar Nasional LP2M UNM, 2019)
Abstract. This research aims to: (1) develop a Web-based lecture monitoring program in the Mathematics Department of FMIPA UNM and (2) test the feasibility of the material and media in a Web-based lecture monitoring program according to aspects of subject matter, pedagogy, auxiliary information, affective consideration, interface, navigation, and robustness.The research approach used is research & development (R&D) using the Plomp model with five stages of development, namely preliminary assessment, design, realization and construction, testing, evaluation and revision and implementation. The instrument used was a feasibility assessment sheet by material experts, a feasibility assessment sheet by media experts, and a feasibility assessment sheet by users. Data analysis uses quantitative descriptive analysis techniques.The results showed that: (1) Web-based lecture monitoring program was categorized as a very feasible program implemented in the Mathematics Department of FMIPA UNM, (2) Web-based lecture monitoring program in the Mathematics Department of FMIPA UNM received a feasibility assessment of 91.67% of the total feasibility aspects from material experts, received a feasibility assessment of 91.65% of the total feasibility aspects by media experts and 86.07% of users namely lecturers Keywords: Lecture Monitoring perkuliahan, Web, feasibility test